MODEL OF INTERNAL WAVES PROPAGATION IN THE OCEAN - KAMILA YASMIN (10112042), RIFADINA
Besides the surface waves, there is another kind of wave that propagates beneath the water surface, named internal waves. Internal waves arises because of the ocean's stratification due to ocean's density and then affected by the earth's rotational movement. The ocean's stratification is measured by a factor named buoyancy frequency. In this final project, internal waves propagation will be learned using a Boussinesq Model or method of vertical modes. There are two assumptions used to build this model, namely Boussinesq approximation and rigid-lid approximation. And then, the study of internal waves propagation can be simplified to two dimensional observation by assuming that the Coriolis force only affect vertically. The model is then applied to simple cases of ocean's stratification to identify the properties of internal waves. After that, the model is applied to the approximation of the real ocean's stratification to give an illustration of the phenomena of internal waves in the ocean.